Extract of Moringa oleifera Leaves: Possible Useful Additives to Enhance Reproductive and Growth Performance of Male Oreochromis niloticus - Naz, Saira; Habib, Syed Sikandar; Acar, Ümit; Majeed, Saima; Kesbiç, Osman Sabri; Ullah, Mujeeb; Khayyam, Khayyam; Khan, Khalid; Mohany, Mohamed; Fazio, Francesco (Central Fisheries Research Institute (SUMAE), 2025)
The current study aimed to test Moringa oleifera leaves extract on the growth and reproductive performance of male Nile tilapia (Oreochromis niloticus). We purchased 420 healthy Nile tilapia (60.32±3.13 g) from the local fish farm for the feeding experiment. The fish were divided in triplicates into seven groups, including the control group, with each group consisting of 60 fish species (20 per glass aquarium). They were maintained in glass aquariums measuring 60×40×35 cm throughout the 60-day feeding trial. Experimental diets, incorporating various concentrations of M. oleifera extracts (0% 2%, 4%, 6%, 8%, 10%, and 12%), were administered to the fish at 3% of their body weight. The results revealed that experimental diets significantly (P<0.05) increased the growth and reproductive performance of the Nile tilapia compared to the control group. M. oleifera significantly (P<0.05) enhanced the levels of testosterone and luteinizing hormones. Furthermore, there was a progressive increase in the overall fertility rate with increasing concentrations of the plant extract. However, the overall performance of the fish decreased with increasing concentrations beyond 12%. The current study concluded that M. oleifera extract can be used to increase the fecundity and growth rate of the fish.
Keywords: Oreochromis niloticus, Moringa oleifera, Sex hormones, Fertility rate, Growth